Absolute frequency measurement of the 87Sr optical lattice clock at NTSC using international atomic time. (1st February 2023) - Lu, Xiaotong; Guo, Feng; Wang, Yebing; Xu, Qinfang; Zhou, Chihua; Xia, Jingjing; Wu, Wenjun; Chang, Hong
Abstract: We report the absolute frequency measurement of the 5 s 2 1 S 0 → 5 s 5 p 3 P 0 transition in 87 Sr optical lattice clock (Sr1) at National Time Service Center. Its systematic frequency shifts are evaluated carefully with a total relative uncertainty of 5.1 × 10 − 17 . The measured absolute frequency is 429 228 004 229 872.91(18) Hz with a relative uncertainty of 4.1 × 10 − 16, with reference to the ensemble of primary and secondary frequency standards published in the Circular T bulletin by BIPM through a global navigation satellite system link.